The Natural History of Flowers - Fogden, Michael; Fogden, Patricia (Book collections on Project MUSE., 2018)
Flowers have played an important role in human culture for thousands of years, symbolizing love, sorrow, and renewal. They provide bursts of color to homes and gardens and convey messages to friends, family, and significant others. Yet we often overlook their real purpose--why do flowers exist and why are they certain colors, shapes, and smells? In nature, flowers are key to healthy ecosystems and play a functional role, increasing a plant's chances for survival. Flowers have evolved to attract specific pollinators and to take advantage of climate variables and animal migration to disperse seeds, ensuring that the species will survive. These fine-tuned methods have evolved over a long period of time, and the importance of pollination and seed dispersal to a healthy environment cannot be overstated. As climate change places pressure on animals and plants, it is also challenging these methods flowers have developed for survival. The Fogdens describe flowers' functions and structures, pollination and seed dispersal methods, and close the book with descriptions of their favorite tropical flowers. The information is illustrated with intimate photographs of flowers and pollinators.